Recurrent follicular ameloblastoma of the maxilla: a case report - Hajar, Hasmawati; Yunus, Barunawaty; Gazali, Mohammad (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This report aims to describe the clinical and radiological characteristics of ameloblastoma. This benign odontogenic tumor rarely occurs in the upper jaw, and to emphasize the importance of using panoramic radiography in confirming the diagnosis. Case Report: A 52-year-old female patient presented with a lump in the right upper jaw that had been present for three months. She reported that a small lump first appeared four years earlier and had gradually increased in size. The patient had a history of surgery to remove a lump and extraction of a right maxillary tooth in 2021, with histopathological analysis (HPA) revealing ameloblastoma. She also reported tenderness in the area and the presence of a salty discharge from the mouth. Panoramic radiography and CT scan revealed a unilocular, homogeneous radiolucent lesion, ovoid with well-defined margins, located in the edentulous posterior right alveolar ridge. The lesion extended superiorly toward the base of the right maxillary sinus and inferiorly toward the crest of the alveolar ridge. The patient underwent an excisional biopsy, with a histopathological examination confirming the diagnosis of a bone tumor (ameloblastoma). This was followed by a segmental maxillectomy in the region of teeth 12–15 under general anesthesia. Ameloblastoma has a high tendency to recur, particularly when conservative management fails to completely remove the tumor. In this case, pathological examination, along with panoramic and CT imaging, confirmed recurrent ameloblastoma. Conclusion: The diagnosis of recurrent follicular ameloblastoma of the maxilla was established through a combination of clinical evaluation, radiographic imaging, and histopathological examination.